Facing the Defeat of Prussia – the Actions of Lithuanian Governorates at the Turn of 1806–1807 - Godek, Sławomir (Vilnius University Open Series, 2024)
In the autumn of 1806, in view of the defeat of Prussia in the clash with France and the approach of Napoleon’s army to the borders of Russia, the Russian authorities became concerned about the loyalty of their Polish subjects. The authorities of the Lithuanian governorates took preventive measures to preclude an uprising movement and preserve public peace. In particular, attempts were made to seal the border. More careful attention was paid to the movement of people, and care was taken to ensure that travellers did not bring anti-government writings into Russia. Intelligence activities were intensified to monitor the disposition of the population. Emperor Alexander I ordered that any insurrectionary uprising be vigorously suppressed by the harshest means, including the use of the army. At the same time, the authorities tried to avoid anything that could fuel popular discontent. By the Emperor’s decision, the use of ukases in the courts, which, in the opinion of the Lithuanian nobility, hindered the conduct of judicial proceedings, was stopped. Attempts were made to introduce strict discipline in military units to prevent abuse of the civilian population. A police force was put on alert to put suspicious people arriving from abroad under surveillance. Signals of contact between Lithuanian residents and the French army were investigated.
Keywords: “The first Polish war”; Lithuanian governorates; security measures